Analisis Pengelolaan Limbah Cair Kelapa Sawit di PT Inti Indosawit Subur - Antoni, Fiki Fadel; Hamzah, Farida Hanum; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
ABSTRACTThis research aims to determine the oil palm liquid waste management system and to obtain palm oil liquid waste management strategy carried out by PT. Inti Indosawit Subur. The research method used in this research is descriptive qualitative and quantitative research methods. The research implementation consists of data collection, data processing, SWOT analysis (strength weekness opportunity treath) and priority strategy setting. Types of data in this study are primary data obtained by conducting interviews and observations and secondary data obtained from literature studies. The data analysis used is SWOT analysis andpair comparison. The results showed that the palm oil mill effluent treatment at WWTP used a waste pool system (Biological Pound System), totaling 11 ponds. The data result of measuring the parameters of the palm oil mill effluent (POME) obtained from UPT Construction Materials Laboratory Riau show the produced palm oil mill effluent is still above the quality standard stipulated in KepMenLH No.5 of 2014. Quadrant SWOT is in quadrant I with value internal factor position index and external is 1.163 and 0.695. Determination of priority strategies which used the pair comparison method is obtains strategy utilization of palm oil mill effluent into biogas and fertilizer according to the regulations for the development of sustainable palm oil processing is the top priority with a score 0.484.Keywords:   POME, SWOT, Pair Comparison